PENGAWASAN, EVALUASI DAN UMPAN BALIK STRATEJIK - Mutakallim, Mutakallim (Inspiratif Pendidikan, 2016)
Controlling is a systematic effort to define a standard of the objectives implementation with the planning goals, designing feedback information systems, comparing the real activity with predetermined standards, defining and measuring the deviations and taking corrective action as necessary. Types of controlling are in forms of; 1) preliminary control; 2) concurrent control; and 3) feedback control. Then, the procedures of controlling are; 1) setting the standard implementation (planning); 2) determining the measurement of program implementation; 3) comparing the implementation of the standard and the deviation analyzer; and 4) taking corrective action. Controlling is important due to changes in the organizational environment, the improvement of organizational complexity, minimizing mistakes, the need of manager to delegate the authority, communicating and assessing the information, and taking corrective action. Designing the controlling process is to formulate the desired results, to set a result guideline, to set the operational standard and results, to assign network information and feedback, to assess the information, and to take corrective action. Strategic fields in controlling are Financial Transactions and Relationship between Manager and Subordinate, and Productive Operations. The the most common controlling tools are Management by Exception), Management Information Systems (MIS), Ratio Analysis and Budgeting.